The Role of Natural Killer Cells in Autoimmune Diseases - Kucuksezer, Umut Can; Aktas Cetin, Esin; Esen, Fehim; Tahrali, Ilhan; Akdeniz, Nilgun; Gelmez, Metin Yusuf; Deniz, Gunnur (Frontiers in Immunology, 2021)
Natural killer (NK) cells, the large granular lymphocytes differentiated from the common lymphoid progenitors, were discovered in early 1970’s. They are members of innate immunity and were initially defined by their strong cytotoxicity against virus-infected cells and by their important effector functions in anti-tumoral immune responses. Nowadays, NK cells are classified among the recently discovered innate lymphoid cell subsets and have capacity to influence both innate and adaptive immune responses. Therefore, they can be considered as innate immune cells that stands between the innate and adaptive arms of immunity. NK cells don’t express T or B cell receptors and are recognized by absence of CD3. There are two major subgroups of NK cells according to their differential expression of CD16 and CD56. While CD16+CD56dim subset is best-known by their cytotoxic functions, CD16-CD56bright NK cell subset produces a bunch of cytokines comparable to CD4+ T helper cell subsets. Another subset of NK cells with production of interleukin (IL)-10 was named as NK regulatory cells, which has suppressive properties and could take part in immune-regulatory responses. Activation of NK cells is determined by a delicate balance of cell-surface receptors that have either activating or inhibitory properties. On the other hand, a variety of cytokines including IL-2, IL-12, IL-15 and IL-18 influence NK cell activity. NK-derived cytokines and their cytotoxic functions through induction of apoptosis take part in regulation of the immune responses and could contribute to the pathogenesis of many immune mediated diseases including ankylosing spondylitis, Behçet’s disease, multiple sclerosis, rheumatoid arthritis, psoriasis, systemic lupus erythematosus and type-1 diabetes. Dysregulation of NK cells in autoimmune disorders may occur through multiple mechanisms. Thanks to the rapid developments in biotechnology, progressive research in immunology enables better characterization of cells and their delicate roles in the complex network of immunity. As NK cells stand in between innate and adaptive arms of immunity and “bridge” them, their contribution in inflammation and immune regulation deserves intense investigations. Better understanding of NK-cell biology and their contribution in both exacerbation and regulation of inflammatory disorders is a requisite for possible utilization of these multi-faceted cells in novel therapeutic interventions.